Polymorphism in the Calpastatin Gene Alters Beef Tenderization in Excitable Cattle: A Preliminary Study - Ana Cláudia da Silva; Patricia Maloso Ramos; Aline Silva Mello César; João Pedro Sousa do Vale; Saulo da Luz e Silva; Eduardo Francisquine Delgado (Animals)
The variability in beef tenderness is a problem for industry and can be difficult to overcome, especially for Bos taurus indicus cattle. The objective of this study was to determine the association between calpastatin (CAST) polymorphisms (Single Nucleotide Polymorphism, SNP) and tenderness in beef of Nellore cattle with divergent temperaments. The animals were genotyped, their temperaments were evaluated, and contrasting groups were formed based on these combined factors (n = 21; calm = 10, 5 AA and 5 AG; and excitable = 11, 4 AA and 7 AG). Carcass pH and temperature decline were monitored (24 h), beef color was measured, and tenderization was assessed by shear force and myofibrillar fragmentation index (MFI) during beef aging (28 d). Calpastatin activity was also determined (24 h). Treatments of temperament and genotype as well as interactions were tested in a randomized block design in a factorial arrangement of 2 (temperament: calm and excitable) × 2 (genotypes: AA and AG). Calm animals harboring the AA allele in the CAST gene were associated with tender beef at 28 d. Excitable cattle or animals harboring the AG allele were associated with less tender beef; excitable AG showed greater calpastatin activity. Excitable animals produced beef with a slower tenderization process and less extension.